2009
DOI: 10.1111/j.1095-8312.2008.01158.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability of hornet cuticular hydrocarbons facilitates chemotaxonomy using museum specimens

Abstract: Cuticular hydrocarbons are key compounds used for insect chemical communication and their species-specificity makes them of great utility to chemotaxonomists. However, very little is known about their long-term stability in relation to their use as reliable taxonomic tools. We compared the cuticular hydrocarbon profiles of fresh extracts from four hornet (Vespa) species with extracts from specimens that were frozen for 1 year and of those stored in insect display boxes for 20 years. Cuticular hydrocarbon profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…A colony usually stays in the same nest for its 20-30 year lifespan (Gordon, 1992). An accumulation of HCs in the midden and on the soil is not unexpected because of the stable nature of these compounds (Martin et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…A colony usually stays in the same nest for its 20-30 year lifespan (Gordon, 1992). An accumulation of HCs in the midden and on the soil is not unexpected because of the stable nature of these compounds (Martin et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The latter can also be extracted using solvents because specimens can be returned to the exhibition. It has been shown that CHCs can remain stable even if specimens have been stored over decades under relatively constant conditions and this also holds true for more unstable unsaturated hydrocarbons (Page et al , 1990; Martin et al , 2009).…”
Section: Taxonomic Benefits Of Using Chcsmentioning
confidence: 94%
“…Long-chain hydrocarbons are unreactive and not susceptible to evaporation in storage; freezing does not significantly cause quantitative or qualitative changes in cuticular hydrocarbon profiles compared to fresh samples [17]. To avoid responses to non-nestmates, forager mimics used at a given colony were made using extracts from ants of the same colony.…”
Section: Methodsmentioning
confidence: 99%